Where is baby? - Rippin, Sally (Allen & Unwin, 2008)
"A board book for the very young - repeats 'Where is Baby?' and gives a different answer each time (In the chair, Over there, etc.)"--Publisher
Keywords: Board books; Babies / Juvenile fiction